Acute effect of kinesio tape on postural control in individuals with functional ankle instability following ankle muscle fatigue - Li, Pan; Wei, Zhen; Zeng, Ziwei; Wang, Lin (Frontiers in Physiology, 2022)
Background: Kinesio taping (KT) is one of the therapeutic interventions in sports medicine practice. The study aims to assess the acute effect of different KT methods on postural control in individuals with functional ankle instability (FAI) after ankle muscle fatigue. Methods: Twenty-eight participants with FAI were recruited to complete maximum voluntary isometric contraction (MVIC) and proprioception of ankle using isokinetic dynamometer, dynamic postural control using Y-balance test and static postural control using a force platform after a fatigue protocol in four taping conditions: facilitatory KT (FKT), ankle balance taping (ABT), sham taping (ST) and no taping (NT). Results: No significant difference was observed for the data MVIC and proprioception after ankle muscle fatigue amongst the four taping treatments. A significant difference in Y-Balance Test was observed amongst the four taping treatments at posterolateral direction (p < 0.001) and posteromedial direction (p < 0.001), suggesting that KT may significantly improve dynamic postural control following ankle muscle fatigue. For Center of pressure (COP) measurements, the mediolateral COP sway range of NT was significantly larger than that of FKT (p = 0.003) and ST (p < 0.001), suggesting that the placebo effect of KT was inevitable. Conclusion: The effect of KT seems increased dynamic postural control in individuals with FAI after ankle muscle fatigue, and this effect is not strongly related to the taping methods. By preventing fatigue-related impairments of postural control, KT may help reduce the risk of injury in individuals with FAI.